Faktor-Faktor yang Berhubungan dengan Kematian Bayi di RSUD Ende - Mogi, Imelda Ririn Obo; Anggraeni, Lina Dewi; Supardi, Sudibyo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: Infant mortality at the age of ≤1 year per 1000 live births is one of the benchmarks for assessing the extent to which the achievement of people's welfare as a result of implementing development in the health sector. This research aimed to identify the factors associated with infant mortality in Ende Hospital. Method: Cross-sectional design was applied in this research. Data retrieval was collected by using medical records in 2017 and 2018. There were 122 mothers had infant mortality aged ≤1 year enrolled in this research with a total population sampling technique. This study used Kendal Tau-b statistical test. Results: The results showed the highest infant mortality occurred at 0-28 days as many as 77,9%. There was a relationship between maternal education (p-value=0.042), asphyxia (p-value=0.014) and infant mortality in Ende Hospital. There was no relationship between maternal age (p-value=0.602), maternal occupation (p-value=0.842), pregnancy danger signs (p-value=0.713), birth weight (p-value=0.587), labor (p-value=0.845), delivery helper (p-value=0.419), place of delivery (p-value=0.354) and infant mortality in Ende Hospital. Health workers need to consider facilities for newborn care, must be able to measure the Apgar Score for asphyxia measurement, and should provide information regarding the importance of conducting ANC examinations to prevent complication during pregnancy and asphyxia.